Effects of high light intensity and spectral variability on maize photosynthesis and growth - Pappert, Isabell; Ühlein, Celine; Jokic, Luca; Kaldenhoff, Ralf (Frontiers in Plant Science, 2025)
This study investigates the effects of ultra-high light intensities and varying light spectra on the photosynthetic efficiency and growth of maize (Zea mays saccharata). Photosynthetic rates, transpiration, stomatal conductance, and leaf temperature were measured under white light, monochromatic light, and their combinations. Assimilation rates increased with light intensities up to 5000 PAR, plateaued around 5500 PAR, and declined beyond 8000 PAR. Red light at 300 PAR yielded the highest assimilation rate under monochromatic conditions, while green light significantly boosted assimilation at higher intensities, peaking at 33.5 µmol m–2s–1 under 4000 PAR. A 50% mix of white and green light at 2000 PAR enhanced assimilation by 14% compared to white light alone. Red light (630 nm) notably promoted photosynthesis in high PAR combinations. However, increasing green light reduced quantum yield, and higher blue light enhanced non-photochemical quenching. These findings suggest that ultra-high light intensities with specific spectral combinations can optimize photosynthesis in maize, though this does not necessarily translate to enhanced overall plant growth.